Studi Tentang Pelaksanaan Kursus Bagi Calon Pengantin di KUA Kec. Kayen Pati - Ahmad Samad (Faculty of Sharia and Law UNISNU Jepara, 2021)
One of the tasks of BP4 is to form a sakinah, mawaddah wa rahmah family and prevent divorce in order to create a noble nation in accordance with Islamic teachings. BP4's most difficult efforts are preventing divorce, resolving disputes, and various household disputes. These disputes are caused by various factors originating from humans themselves and many more external factors. While the positive impact of the BP4 Prospective Bride Course in Kayen District is the preparation of the bride and groom related to the material that has been delivered. Based on the results of interviews that the authors did, the prospective brides admitted that this pre-marital guidance was very useful for them. Because there is a lot of knowledge that they didn't know before, after following the guidance they understand, and they want to always try their best to improve the quality of marriage and create a happy and prosperous family, eternal according to Islamic guidance. The success of BP4 is the awareness of the partner, of the rights and responsibilities as a husband and wife, so that in married life an attitude of mutual understanding is formed, and mutual respect is created by creating a sakinah family so as to minimize the occurrence of divorce.Salah satu tugas BP4 adalah membentuk keluarga sakinah, mawaddah wa rahmah serta mencegah perceraian guna mewujudkan bangsa yang mulia sesuai dengan ajaran Islam. Usaha BP4 yang paling berat adalah mencegah perceraian, menyelesaikan percecokan, pertikaian rumah tangga yang sangat banyak ragamnya. Percecokan tersebut ditimbulkan oleh berbagai macam faktor yang berasal dari manusia itu sendiri dan lebih banyak lagi faktor-faktor dari luar. Sedangkan dampak positif dari Kursus BP4 Calon Pengantin di Kecamatan Kayen yakni adanya persiapan diri dari calon pengantin terkait dengan materi yang telah disampaikan. Berdasarkan hasil wawancara yang penulis lakukan bahwa para calon pengantin mengaku bimbingan pra nikah ini sangat bermanfaat untuk mereka. Karena banyak pengetahuan yang sebelumnya tidak mereka ketahui setelah mengikuti bimbingan menjadi mengerti, serta mereka ingin senantiasa berusaha semaksimal mungkin untuk meningkatkan kualitas perkawinan serta mewujudkan keluarga bahagia dan sejahtera, kekal menurut tuntunan Islam. Keberhasilan BP4 adalah adanya kesadaran dari pasangan, akan hak dan tanggung jawab sebagai seorang suami dan istri, sehingga dalam kehidupan berumah tangga terbentuk sikap saling pengertian, serta saling menghargai dengan tercipta keluarga yang sakinah sehingga dapat meminimalisir perceraian.